2013
DOI: 10.1139/cjfas-2012-0474
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns in total phosphorus in south-central Ontario streams: the role of wetlands and past disturbance

Abstract: Unraveling the cause(s) of declines in total phosphorus (TP) observed over the past three decades across many forested catchments in central Ontario remains a research priority. The objectives of this paper were firstly to test the assumption that weir water chemistry is representative of catchment changes at two adjacent headwater streams that have shown declines in TP and secondly use long-term measurements of weir water quality (1980–2008) to identify potential drivers of TP declines. Longitudinal measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Despite naturally oligotrophic conditions in the region, TP concentrations have declined in approximately ⅔ of the monitored lakes and streams in the region over the past three decades (Eimers et al 2009;Palmer et al 2011;O'Brien et al 2013), and this surprising trend is the focus of new research into causes of TP declines in surface waters. Declines in stream TP have been observed at both upland and wetland draining streams, although the largest declines have occurred in wetland-dominated catchments (Eimers et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite naturally oligotrophic conditions in the region, TP concentrations have declined in approximately ⅔ of the monitored lakes and streams in the region over the past three decades (Eimers et al 2009;Palmer et al 2011;O'Brien et al 2013), and this surprising trend is the focus of new research into causes of TP declines in surface waters. Declines in stream TP have been observed at both upland and wetland draining streams, although the largest declines have occurred in wetland-dominated catchments (Eimers et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although O'Brien et al (2013) did not specifically consider disturbance within wetlands, disturbance in headwater wetlands may be particularly important since wetlands in the region are known to act as sources of TP mainly because of release from organic soils and vegetation (Devito and Dillon 1993). Examples of disturbances that impact biological cycling of P in wetlands include timber harvesting, fires, floods, or insect infestations (McEachern et al 2000;Ensign and Mallin 2001), although most studies on wetland disturbance focus on the effects on nitrogen (N) export (Bernhardt et al 2003;Cleveland et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to wetlands, riparian zones have been noted as important sources of TP export in this landscape (Carlyle and Hill 2001;O'Brien et al 2013) and seasonal changes in wetland/riparian water table height have been associated with changes in [TP] in pore and surface waters (Devito and Dillon 1993). In a recent study at Harp Lake, O'Brien et al (2013) showed that TP concentrations in streams were strongly influenced by organic soils in nearstream riparian areas and argued that seasonal variation in [TP] could be explained by processes operating in these organic-rich riparian soils.…”
Section: Patterns In Stream Total Phosphorusmentioning
confidence: 99%
“…In a recent study at Harp Lake, O'Brien et al (2013) showed that TP concentrations in streams were strongly influenced by organic soils in nearstream riparian areas and argued that seasonal variation in [TP] could be explained by processes operating in these organic-rich riparian soils. However, whilst processes occurring in organic soils could explain seasonal patterns, the long-term pattern of declining [TP] could not be attributed to changes in redox chemistry.…”
Section: Patterns In Stream Total Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation